Wnt9a signaling is required for joint integrity and regulation of Ihh during chondrogenesis - Später, Daniela; Hill, Theo P.; O'Sullivan, Roderick J.; Gruber, Michaela; Conner, David A.; Hartmann, Christine (Development (Cambridge), 2006)
Joints, which separate skeleton elements, serve as important signaling centers that regulate the growth of adjacent cartilage elements by controlling proliferation and maturation of chondrocytes. Accurate chondrocyte maturation is crucial for endochondral ossification and for the ultimate size of skeletal elements, as premature or delayed maturation results predominantly in shortened elements. Wnt9a has previously been implicated as being a player in joint induction, based on gain-of function experiments in chicken and mouse. We show that loss of Wnt9a does not affect joint induction, but results to synovial chondroid metaplasia in some joints. This phenotype can be enhanced by removal of an additional Wnt gene, Wnt4 , suggesting that Wnts are playing a crucial role in directing bi-potential chondro-synovioprogenitors to become synovial connective tissue, by actively suppressing their chondrogenic potential. Furthermore, we show that Wnt9a is a temporal and spatial regulator of Indian hedgehog ( Ihh ), a central player of skeletogenesis. Loss of Wnt9a activity results in transient downregulation of Ihh and reduced Ihh-signaling activity at E12.5-E13.5. The canonical Wnt/Î²-catenin pathway probably mediates regulation of Ihh expression in prehypertrophic chondrocytes by Wnt9a, because embryos double-heterozygous for Wnt9a and Î²-catenin show reduced Ihh expression, and in vivo chromatin immunoprecipitation demonstrates a direct interaction between the Î²-catenin/Lef1 complex and the Ihh promoter.